Disappearance of Crohn's Ulcers in the Terminal Ileum after Thalidomide Therapy - NB Hershfield (Canadian Journal of Gastroenterology)
A case of intractable Crohn's disease unresponsive to all forms of therapy, including multiple operations and medication, is reported. The patient responded to thalidomide and this has resulted in the disappearance of the disease in the neoterminal ileum. Thalidomide may be a valuable treatment in intractable cases of Crohn's disease. The case is presented in a chronological fashion and endoscopic photographs documenting the disappearance of the disease are presented.